Hubungan Pemahaman NKRI dan Kesadaran Akan Keragaman Budaya Lokal dengan Sikap Cinta Tanah Air di Kelas V Sekolah Dasar di Gugus VI Kecamatan Sukaraja Kabupaten Bogor - Djaja Maksum (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
This study aims to determine the relationship between students' understanding of the Unitary Republic of Indonesia and awareness of the diversity of local culture with the attitude of love homeland students. Research method used in this research is survey method with correlation technique. The research was conducted on all grade students in all elementary school of Gugus VI Kecamatan Sukaraja, Bogor regency, West Java Province, which had an affordable population of 270 students in 8 elementary schools. The sampling technique used is proportional random sampling technique as many as 40 respondents Based on the results of research and discussion, the conclusion obtained is the understanding of NKRI has a positive relationship with the power of strong relationship with the attitude of love homeland.